1967
DOI: 10.1113/jphysiol.1967.sp008370
|View full text |Cite
|
Sign up to set email alerts
|

The stoicheiometry of sodium ion movement from frog muscle

Abstract: SUMMARY1. Further measurements of the consumption of high energy phosphate during the active extrusion of sodium ions from frog muscle were made in the presence of iodoacetate or dinitrofluorobenzene.2. In the presence of iodoacetate the consumption of ATP for phosphorylation of hexose is appreciable and so a deduction is made from the total ATP consumption during the ion movement.3. In the presence of dinitrofluorobenzene the deamination of adenosine monophosphate makes the changes in adenosine triphosphate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1969
1969
1991
1991

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Thus Baker (1965) calculated that for the Na pump in crab axons the ATP:Na ratio was close to 1: 3, and Baker & Shaw (1965) concluded that this ratio probably also applied to squid giant axons. For frog muscle, Dydynska & Harris (1966) and Harris (1967) showed that the ATP:Na ratio was also close to 1: 3. Since this ratio is the same as in red blood cells, it seems reasonable to suggest that the Na: K ratio is also the same, and that the ratio for the Na pump in snail neurones might well be 3Na: 2K.…”
Section: Discussionmentioning
confidence: 91%
“…Thus Baker (1965) calculated that for the Na pump in crab axons the ATP:Na ratio was close to 1: 3, and Baker & Shaw (1965) concluded that this ratio probably also applied to squid giant axons. For frog muscle, Dydynska & Harris (1966) and Harris (1967) showed that the ATP:Na ratio was also close to 1: 3. Since this ratio is the same as in red blood cells, it seems reasonable to suggest that the Na: K ratio is also the same, and that the ratio for the Na pump in snail neurones might well be 3Na: 2K.…”
Section: Discussionmentioning
confidence: 91%
“…If J, in Table III decreases exponentially with the time constant r = 30 min, its average value during the first hour in recovery solution is 57% of its initial value, or between 10 and 16 pmoles/cm2 per sec. Under similar conditions, but with dinitrofluorobenzene in the solution (which inhibits ATP synthesis) muscle ATP is hydrolyzed at a rate of 7.7-18.6 mM/kg per hr (Dydynska and Harris, 1966;Harris, 1967). For r = 40 u and for fiber water = 650 cm2/kg wet weight, J, = 6-12 pmoles ATP/cm2 per sec over 1 hr and is within the range given in Table III.…”
Section: Discussionmentioning
confidence: 56%